A guideline: implementation of the flipped classroom teaching approach in learning statistics / Siti Hasma Hajar Mat Zin - Mat Zin, Siti Hasma Hajar (Universiti Teknologi MARA, Kedah, 2023)
Nowadays, statistics can be viewed as the most important science in the world because every other science depends on statistics for its practical applications. This has led to making statistics a core subject in Malaysian higher education institutions and requiring students from other courses to take this subject in their studies. However, the majority of students may find it challenging to use statistics and understand the results. In order to reduce the challenges, lecturers should motivate their students and implement a new teaching strategy in their lessons with the intention of having more adaptive classes. A flipped classroom teaching approach is one of the methods to solve this problem. The flipped classroom provides students direct access to online educational platforms' video lectures, slideshows, and other instructional resources. The combination of classroom activities and online learning experiences outside the class will enhance students’ learning motivation and attitude more than traditional teaching. It solves the majority of problems faced by absent students who are missing classes by referring to the recorded video, which can be accessed anytime and anywhere. Based on one survey, we found that more than half (74%) of the respondents opted for the flipped classroom, while only 26% of the respondents preferred the traditional classroom. The main reason is that the recorded videos can be watched repeatedly by students at their own pace. Therefore, this guideline is meant to help educators plan for a flipped classroom in preparing materials for the statistics subject and choosing tools that suit this approach.